241 Bovine Respiratory Disease: Sex matters. (7th December 2018) - Burdick Sanchez, N; Broadway, P; Carroll, J; Word, A; Littlejohn, B; Paulus Compart, D
Abstract: To evaluate a potential sexual dimorphic innate immune response to respiratory disease, 8 steers and 7 heifers (BW=280 ± 4 kg) were subjected to a combined viral-bacterial respiratory disease challenge utilizing BHV-1 (intranasal; 1.0x10 8 PFU/mL/nostril) at -72h and Mannheimia haemolytica (MH ; intratracheal; 1.3x10 7 CFU/hd) at 0h. Following MH administration, serum was collected every h for 8h, and every 12h from 12 to 72h, and at 168h and was analyzed for cytokines. Whole blood was analyzed every other h from 0 to 8h, every 12h from 12 to 72h, and at 168h for hematology variables. Body temperature, measured from -72 to 69h via indwelling rectal or vaginal temperature monitoring devices, was greater in steers compared to heifers (40.06 vs. 39.60 ± 0.11 o C; P =0.008). Serum IL-4 was greater in steers than heifers (14.7 vs. 2.8 ± 2.7 pg/mL; P =0.007), while there was no difference ( P ≥0.10) in IL-6 or IFN-γ. There was a tendency ( P =0.09) for a treatment by time interaction for total white blood cells (WBC ), such that WBC were greater in steers than heifers at -72h, but were reduced in steers compared to heifers from 36 to 60h post-MH challenge. Neutrophils were elevated in steers compared to heifers from 0 to 4h, at 6h, and from 8 to 12h, but were reduced in steers compared to heifers at 168h ( P =0.02). Lymphocytes were reduced in steers compared to heifers at 12h and from 36 to 60h post-MH ( P PP=0.005). These data demonstrate distinct differences in the innate immune response following a BRD challenge such that steers produced an early response while the response in heifers was delayed.